Relating microstructure to defect behavior in AA6061 using a combined computational and multiscale electron microscopy approach. (1st August 2019) - Yoo, Yung Suk Jeremy; Lim, Hojun; Emery, John; Kacher, Josh
Abstract: In this study, a multiscale electron microscopy-based approach is applied to understanding how different aspects of the microstructure in a notched AA6061-T6, including grain boundaries, triple junctions, and intermetallic particles, promote localized dislocation accumulation as a function of applied tensile strain and depth from the sample surface. Experimental measurements and crystal plasticity simulations of dislocation distributions as a function of distance from specified microstructural features both showed preferential dislocation accumulation near intermetallic particles relative to grain boundaries and triple junctions. High resolution electron backscatter diffraction and site-specific transmission electron microscopy characterization showed that high levels of dislocation accumulation near intermetallic particles led to the development of an ultrafine sub-grain microstructure, indicative of a much higher level of local plasticity than predicted from the coarser measurements and simulations. In addition, high resolution measurements in front of a crack tip suggested a compounding influence of intermetallic particles and grain boundaries in dictating crack propagation pathways. Graphical abstract: Image 1